Considering the Effect of Motorcyclist Risk Tolerance in Accident Risk Management: A Preliminary Study - Siti Malkhamah; Latif Budi Suparma; Don Gaspar Noesaku da Costa (Civil Engineering Dimension, 2018)
Negative perceptions about accident are usually associated with speeding behavior. However, risk perception has not been considered in accident risk management. It is accepted as a personality matter, thus the number of accidents per year was used as accident risk tolerance indicator. Consequently, due to insufficient measurable indicators, it would be difficult to prevent the increasing speeding behavior. This paper discusses the improvement of accident risk tolerance indicators, i.e. safety factor and margin of safety, and their possible usage in speed management policies. These indicators were built based on the correlation between the results of interview and braking maneuver test. From this combine approach, using aggregated-individual and expert acceptance models, it was found that risk tolerance arose because motorcyclists accepted both the advantages and disadvantages gained from speeding, obtained through their riding frequency, duration of riding and/or accident involvement experienced. However, inappropriate speed due to miss-perception toward braking capability should be avoided. Inversely, an appropriate speed management should consider their travelling expectation